Mortality causes and health spending by gender and health conditions in octogenarians, nonagenarians and centenarians in Colombia - Oscar Espinosa; Valeria Bejarano; Isabella Franky; Sandeep Pagali; Michael Drummond; Oscar H. Franco (Scientific Reports)
Abstract This document determines the causes of mortality (2008–2022) and calculate per capita health expenditure (2013–2021) in octogenarians, nonagenarians and centenarians in the Colombian population, considering year, gender and age group. For this nationwide retrospective descriptive observational study, epidemiological regions, urban/rural areas and morbidities were also studied. A mean of 75,552 deaths was observed from 2008 to 2022. Deaths were higher due to ischemic heart disease, COVID-19, chronic obstructive pulmonary disease, cancer, and cerebrovascular diseases in the oldest old Colombian population with urban areas having higher mortality rates than rural areas (an average of 948 (min: 847, max: 1207) against 630 (min: 558, max: 789) per 10,000 people, respectively). Conditions of cerebrovascular diseases, cancer, influenza pneumonia and chronic obstructive pulmonary disease were the most expensive in health care, summing above 5000 purchasing power parity USD on average (min: 2234, max: 7539). These conditions, along with hypertension and diabetes mellitus, were the most frequently recorded. COVID-19 incurred higher health expenditure in rural areas compared to urban areas (1090 vs. 519 purchasing power parity USD respectively). High prevalence (14·3%) and medical attention (16·8 health care utilisations per capita) were shown for organic mental disorders. Our analysis found that centenarians survived COVID-19 more than octogenarians and nonagenarians, with several hypotheses attributing this to their immune profiles. We found high expenditure on HIV/AIDS among older males suggesting the need for further study on sexually transmitted diseases prevention in this population. Lastly, Alzheimer’s disease, particularly in rural areas, had substantial expenditure. Therefore, neurodegenerative diseases and the impact of stressful events on mental health must be priorities for the health system to ensure adequate resource management.